Contradictions and Interventions in Health IS - Andy Weeger; Heinz-Theo Wagner; Heiko Gewald; Tim Weitzel (Business & Information Systems Engineering, 2021)
The study analyzes data collected in two case studies in the healthcare industry, which is characterized by a variety of social and technical elements forming an activity system where all elements interact with each other. The findings indicate that many problems emerging during the implementation of a health information system can be traced back to contradictions between elements of the activity systems that are created or amplified by the new IS. The authors find that some contradictions are latent and become salient when introducing a new IS, while other contradictions are (unintentionally) newly created. Also, the study shows that contradictions are more complex than hitherto assumed and often concern more than two elements of a healthcare activity system. In a similar vein, effective interventions geared toward countering these contradictions are found to account for additional complexity while not always achieving their goal. Drawing on activity theory, the authors develop a framework to coherently synthesize the findings. The study can help increase the understanding of the IS's role within an activity system and help guide IS implementation projects aimed at avoiding unintended consequences.
Keywords: 000; Health information systems (HIS); Post-implementation; Contradictions; Activity theory; Hospital; Healthcare